2016
DOI: 10.1186/s12906-016-1188-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of Bon-santé cleanser® polyherbal in male Wistar rats

Abstract: BackgroundThe potential harm of medicinal herbs has been recently observed following herbal toxicity studies after ingestion of polyherbal remedies. This was the rationale for the food and drug regulatory agency decision for thorough safety evaluation of herbal medicines. Androgenic, antipyretic, analgesic and anti-inflammatory potentials as well as chemical compositions of extracts of massularia acuminata, terminalia ivorensis, anogeissus leiocarpus and macuna pruriens respectively have been documented. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…The extraction and formulation procedures complied with the regulatory manual of NAFDAC. In this context, a single capsule of BSC (total content 442 mg) was prepared as previously reported 32 and administered via oral gavage according to standard toxicological guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extraction and formulation procedures complied with the regulatory manual of NAFDAC. In this context, a single capsule of BSC (total content 442 mg) was prepared as previously reported 32 and administered via oral gavage according to standard toxicological guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Progressive sperm motility, sperm count, and sperm viability were then examined under the microscope attached to a Celestron ® Digital Microscope Imager (Torrance, CA 90503) and viewed under X40 objective according to the method described by Raji et al 34 and modified by Kale and Awodele. 32 Epididymal sperm motility was assessed by calculating motile spermatozoa per unit area and was expressed as percentage motility. Epididymal sperm count was done using the improved Neubauer hemocytometer and expressed as million/ml of suspension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An incision of about 1 mm was made in the caudal epididymis to liberate its spermatozoa into the saline solution. Progressive sperm motility, sperm count, and sperm viability were then examined under the microscope attached to a Celestron® Digital Microscope Imager (Torrance, CA 90503) and viewed under X40 objective as described elsewhere [ 18 ]. Epididymal sperm motility was assessed by calculating motile spermatozoa per unit area and was expressed as percentage motility.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that dietary supplements are now being used to prevent and treat various diseases [ 15 , 16 ]. However, a number of adverse events have been reported over the past few years with the use of herbs and herbal products [ 17 , 18 ]. Furthermore, concerns over drug-herbs interactions and irrational drug use (high dose) of CAM have arisen.…”
Section: Introductionmentioning
confidence: 99%